Bibliometry of collaboration and impact of the Revista de Biología Tropical (Web of Science 2003-2012) - De Filippo, Daniela (2016)
The activity analysis of a scientific journal is relevant to know the evolution of its characteristics over time. In this paper, results of a bibliometric study of the Revista de Biología Tropical/International Journal of Tropical Biology and Conservation (Costa Rica) are presented. The goal of this study was to describe the main characteristics of its scientific production, and analyze its level of collaboration and its impact between the years 2003-2012. Data was derived from the Web of Science (Thomson-Reuters), and the relationship among authors and coauthors, institutions and countries, and their links with the citations received were analyzed for that period. Descriptive statistics about production (number of documents per year, institution and country), collaboration (authorship index, collaboration among institutions and countries) and impact (IF, position in JCR and number of citations received) were collected. Results showed that the journal has published 1 473 papers in this period, in similar proportions English and Spanish. Mexico, Costa Rica, Venezuela and Colombia are the most common countries of origin, with the Universidad of Costa Rica, Universidad Autónoma de Mexico and the University of Puerto Rico as the most common leader institutions. Collaboration between authors, institutions and countries has shown an increasing trend over the last decade. The co-author index was 3.07 per document, 63 % of publications included 2 or more institutions, and 22 % of the papers were product of international collaboration. The most common collaboration link was between Costa Rica and the United States of America. The impact factor has been oscillating during this last decade, reaching a maximum in 2012 (IF JCR = 0.553). Besides, 10 % of the most cited papers concentrated half of the citations received by the journal, and have a very high number of citations, compared with the journal mean. The main countries that cite the journal were USA, Brazil, Mexico, Argentina and Costa Rica. Data showed an increasing collaboration between authors, institutions and countries, and a direct relationship between the increase of this collaboration and the received impact.